Non-Canonical Processing of Arabidopsis pri-miR319a/b/c Generates Additional microRNAs to Target One RAP2.12 mRNA Isoform - Sobkowiak, Lukasz; Jarmolowski, Artur; Karlowski, Wojciech; Szweykowska-Kulinska, Zofia (Frontiers in Plant Science, 2012)
Arabidopsis miR319a/b/c primary transcripts are unusual because of the presence of a long stem and loop structure containing functional miR319a/b/c molecules. In our experiments carried out using HTS, we have shown that additional microRNAs, miR319a.2/b.2/c.2 are generated from the upper part of the same hairpin structure. We have also found cognate miRNAa.2*/b.2* to be present in the HTS results with considerably lower number of reads. Northern hybridization revealed thatmiR319b.2 is mainly expressed in 35-day old plant rosette leaves, as well as in stem and inflorescences of 42 and 53 day-old plants. Moreover, it carries multiple signatures of a functional microRNA: its biogenesis is Hyl-1 dependent, (ii) it is incorporated in substantial amount into RISC complexes containing Ago1, Ago2, or Ago4 protein, (iii) 24nt long species of miR319b.2 have been found in inflorescences where they are more abundant than 21nt miR319b.2 species,(iv) it is present in various ratios to miR319b during plant development, suggesting the existence of regulatory mechanism responsible for its biogenesis/processing, (v) there is observed cross-species conservation of the miR319a/b/c stem nucleotide sequence extending beyond mature microRNA region, (vi) all evidence suggests that intron-containing RAP2.12 mRNA isoform is the target for miR319b.2. All these features prompt us to claim miR319b.2 as a functional microRNA molecule.